Analysis of students' thinking level in solving Pythagoras' theorem problems based on Van hiele's theory - Wulandari, Sari; Syahbana, Ali; Tanzimah, Tanzimah; Shang, Yilun; Weinhandl, Robert; Sharma, Rajinder (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The aims of this analysis are to explain the level of thinking of grade VIII students at SMP Negeri 1 Talang Ubi in solving Pythagorean Theorem questions based on Van Hiele's theory. The research approach used in this analysis is descriptive qualitative case study research. The subjects of this research were three students of grade VIII of SMP Negeri 1 Talang Ubi, South Sumatera Indonesia. The three students were chosen based on their test answers on the Pythagorean Theorem material, with one being a high-ability student, one being a medium-ability student, and one being a low-ability student. The study's data collection techniques included assessments, interviews, and documentation. Techniques for data processing include data reduction, data presentation, and conclusion. The findings revealed that high-ability students could complete all four stages of Van Hiele's thinking: imagination, interpretation, informal deduction, and deduction. Moderate students achieved three levels of Van Hiele's thinking, including visualization, analysis, and informal deduction, while low-ability students achieved only one level of Van Hiele's thinking, visualization.